Pension Reform and Macroeconomic Stability in Latin America - Roldos, Jorge (Washington, D.C. : International Monetary Fund, 2007)
This paper reviews macroeconomic aspects of pension reforms in Latin America, focusing on financial market stability and fiscal sustainability. Concentration of pension fund portfolios in government bonds remains high, and the lack of new investment alternatives has distorted asset prices. Countries have gradually liberalized investments abroad, but remain wary of the impact on foreign currency markets. The fiscal costs of the transition to funded systems have been higher than expected, and have contributed to high debt levels. The paper highlights the importance of coordinating changes in portfolio limits with debt management policies and measures to develop securities markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet